Growth, carcass characteristics and meat quality of Muzaffarnagari lambs at various stages under intensive and semi-intensive management - DAS, ARUN K; DASS, GOPAL; SINGH, N P (The Indian Journal of Animal Sciences, 2011)
Male Muzaffarnagari lambs (28) were reared under intensive and semi-intensive management system, to asses their growth attributes, carcass characteristics and meat quality. Average daily weight gains were significantly higher in the intensive management system in the age group of 2-6, 6-9 and 2-9 months, respectively. Lambs reared under intensive system attained 35.27 kg slaughter weight as against 22.52 kg at 6 months of age leading to 56.62% increase in slaughter weight, whereas at 9 months of age, it was 44.22%. Hot carcass weight and dressing% were significantly higher in lambs managed under intensive system in both the age groups. Carcass measurements including breast fat and back fat thickness, OR measurement, leg circumference and loin eye area were also different between the management systems in both the age groups. Similarly the depot fat weight was significantly higher under intensive management system in both the age groups. Percentage of separated lean and fat significantly increased and bone% declined significantly in the carcass of intensively managed lambs for 6 months compared to semi-intensively commensurating with significantly higher back fat and breast fat thickness in the carcass of former group. Meat physico-chemical qualities pH, water holding capacity and cooking loss were not significantly different between management systems and in both the age groups. The meat of intensively managed lambs had significantly lower moisture and higher fat content but similar protein and ash contents compared to meat of semi-intensively managed lambs in both the age groups. Carcass chemical fat (CCF), total body fat (TBF) and fat free carcass weight were significantly higher in meat of lambs managed under intensive system at 6 months of age, whereas at 9 months of age, CCF, TBF and fat free carcass weight were still higher in meat of intensively managed lambs. It was concluded that Muzaffarnagari sheep are more suitable for quantity and quality mutton production at 6 months of age and targeting for production of heavier weight carcass for more meat production would be uneconomical. Â